Desenvolvimento de ferramenta de apoio à tomada de decisão edilícia considerando critérios de desempenho térmico e aquecimento de água - Rejane Magiag Loura (2012)
Problem: Nowadays it is relevant to improve the thermal-energy performance in housing envelopes and heating water systems, assuming or not an acceptable increase in costs. Motivation: This issue is due to the growth of electricity demand expected in the residential sector for the next two decades. It is worth to focus on the two more significant end-uses in housing energy consumption: thermal comfort and water heating for bathing. Objective: To develop a multicriteria decision tool to assist in decision making about housing envelope solutions and heating water system during the initial stages of the building venture, considering the thermal-energy performance and the solutions costs. Methodology: It associates national energy policy issues, building costs, thermal-energy performance simulation and multicriteria analysis. Then creates a database that puts together the information that will be analyzed by the ELECTRE-III method based on five criteria: (i) percentage of thermal comfort hours (ii) cooling degree-hours, (iii) percentage of envelope variation costs, (iv) governmental incentives for heating water technologies and (v) complexity level of installation of water heating system. The analysis result is a ranking of the building solutions evaluated. Results: It verified the methodology and software applicability that was developed to overcome the presented problem applying in hypothetical case considering the real estate market of Rio de Janeiro. Thus, it becomes possible to list the building solutions performance considering thermal-energy criteria and costs during the initial stages of design. This is helpful for designers and investors (private and public) in decision processes because the method offers a solutions ranking based on in costs and benefits, which certainty helps to choose solutions with better thermal-energy performance solutions within the budgeted cost